2017
DOI: 10.1002/jcp.26225
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone inhibits cancer cell growth through STAT3 inhibition and enhanced AIF expression via a PPARγ‐independent pathway

Abstract: Pioglitazone is an anti-diabetic agent that belongs to the thiazolidinedione class, which target peroxisome proliferator-activated receptor γ (PPARγ), a transcription factor in the nuclear receptor family. Different cancer cells expressing high levels of PPARγ and PPARγ ligands induce cell cycle arrest, cell differentiation, and apoptosis. However, the mechanisms underlying these processes remain unknown. Here, we investigated the mechanism underlying pioglitazone-induced apoptosis in human cancer cells. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Other evidences showed that troglitazone induces apoptosis of lung cancer cell line NCI-H23 via a mitochondrial pathway through the activation of ERK1/2 [12]. In addition to anti-proliferative effects, TZD can sensitize cancer cells to anticancer therapies enhancing the cytotoxic effect of cisplatin and oxaliplatin by suppressing survivin and increasing the apoptosis-inducing factor (AIF) expression [20]. Among TZDs, pioglitazone was approved for the treatment of type 2 diabetes and continues to be recommended in current guidelines since pioglitazone bladder cancer concerns have been largely attenuated by recent evidences [21].…”
Section: Discussionmentioning
confidence: 99%
“…Other evidences showed that troglitazone induces apoptosis of lung cancer cell line NCI-H23 via a mitochondrial pathway through the activation of ERK1/2 [12]. In addition to anti-proliferative effects, TZD can sensitize cancer cells to anticancer therapies enhancing the cytotoxic effect of cisplatin and oxaliplatin by suppressing survivin and increasing the apoptosis-inducing factor (AIF) expression [20]. Among TZDs, pioglitazone was approved for the treatment of type 2 diabetes and continues to be recommended in current guidelines since pioglitazone bladder cancer concerns have been largely attenuated by recent evidences [21].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PPAR control may have significant promise for breast cancer prevention. Recently, PPAR ligands were shown to inhibit the growth of a variety of transformed cells (9,12,13); hence signals that modulate PPAR activity may serve a primary role in regulating breast cancer metastasis and may be major targets for treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are conflicting reports of caspase involvement in apoptosis induced by PPARγ agonists in cancer cells. Pioglitazone-mediated apoptosis occurs via a caspase-independent pathway in bladder cancer cells ( 5 ). In contrast, pretreatment of PC-3 cells with z-VAD-fmk inhibited PPARγ agonist-mediated apoptosis, indicating the involvement of the caspase-dependent pathway in prostate cancer ( 40 ).…”
Section: Discussionmentioning
confidence: 99%